2002
DOI: 10.1034/j.1399-3046.2002.1o040.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcome in high‐risk patients after renal transplantation in early childhood

Abstract: Patient and graft survival rates of pediatric renal transplant recipients are currently excellent, but there are few reports regarding the long-term neurodevelopmental outcome after renal transplantation (Tx) in early childhood. Children with renal failure from infancy would be expected to have a less favorable developmental prognosis. We report the neurodevelopmental outcome in 33 school-age children transplanted between 1987 and 1995 when < 5 yr of age. We prospectively performed a neurological examination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(146 citation statements)
references
References 33 publications
7
139
0
Order By: Relevance
“…One study that examined motor performance in young children using the Bayley Scales of Infant Development found that motor development was abnormal in 24% of children transplanted in early childhood [41]. Neurological co-morbidity was the most negative predictor of poor motor performance [41]. It has been suggested that mutations in the CTNS gene may influence brain development [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study that examined motor performance in young children using the Bayley Scales of Infant Development found that motor development was abnormal in 24% of children transplanted in early childhood [41]. Neurological co-morbidity was the most negative predictor of poor motor performance [41]. It has been suggested that mutations in the CTNS gene may influence brain development [42].…”
Section: Discussionmentioning
confidence: 99%
“…Muscular hypotonia can be associated with poorer motor perfor- mance, in particular with static balance tasks. One study that examined motor performance in young children using the Bayley Scales of Infant Development found that motor development was abnormal in 24% of children transplanted in early childhood [41]. Neurological co-morbidity was the most negative predictor of poor motor performance [41].…”
Section: Discussionmentioning
confidence: 99%
“…Some NPHS1 patients who received a transplant in infancy have abnormal electroencephalograms and problems in cognitive performance at school age. These, however, are associated with the pretransplantation complications, such as hypertensive crises, seizures, and cerebral infarcts (38). Approximately 80% of NPHS1 children attend normal school.…”
Section: Tissue Expression Of Nephrinmentioning
confidence: 99%
“…The mean intelligent quotient (IQ) was 87, and 6-24 % showed impairment in neuropsychological tests. About 80 % of the children attended normal school and 76 % had normal motor performance [86]. In another study, 50 children transplanted at an early age were assessed at a mean age of 11.1 years.…”
Section: Neurocognitive Developmentmentioning
confidence: 99%